Development and characterization of micronutrient fortified sesame cake flour supplemented doughnuts: Characterization of sesame cake flour supplemented doughnuts - Abbas, Sabiha; Sharif, Mian Kamran; Tauseef Sultan , Muhammad; Nisar Ahmad , Atif; Junaid Anwar, Muhammad; Zhu, Meijun (Progress in Nutrition, 2021)
This study evaluated the quality of doughnuts prepared by using sesame cake flour fortified with micronutrient premix (comprising Fe, Zn, vitamin A, C and folic acid). Doughnuts developed with sesame cake flours (0, 10 and 20%) were analyzed for nutrient composition, mineral profile, physical properties, calorific value and storage stability. It was evident from results that supplementation with 20% sesame cake flour improved the protein (10.20% to 24.85%) and ash content. However, substantial decrease was noticed for carbohydrates. Similarly, mineral contents (P, Ca and Mg) also increased with increasing supplementation level of sesame cake flour. Likewise, increasing trend was observed for physical properties like hardness, cohesiveness and chewiness. Calories were also raised from 350.07±3.47 to 394.00±7.12Kcal/100g. Color analysis showed that L* values decreased as darker (brown) color was observed in doughnuts due to caramelization reaction between the amino acids and sugars with the addition of sesame cake flour. Storage analyses also showed significant differences between 100% wheat doughnuts and sesame cake flour supplemented samples regarding Peroxide value, Thiobarbituric Acid Number and Mold growth. It was concluded that 20% supplementation of wheat flour with sesame cake flour produced doughnuts with superior quality and better overall acceptability.